2022
DOI: 10.1186/s12964-022-00875-7
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase TRIM15 facilitates non-small cell lung cancer progression through mediating Keap1-Nrf2 signaling pathway

Abstract: Background Recent studies have indicated that some members of the tripartite motif (TRIM) proteins function as important regulators for non-small cell lung cancer (NSCLC), However, the regulatory mechanism underpinning aberrant expression of TRIM in NSCLC remains unclear. Here we report that TRIM15 plays important roles in NSCLC progression through modulating Keap1-Nrf2 signaling pathway. Methods TRIM15 expression was evaluated by western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…We previously reported that TRIM15 promotes APOA1 ubiquitination and degradation in pancreatic cancer [ 11 ]. Liang et al reported that TRIM15 directly targets Keap1 for degradation [ 12 ]. In addition to enhancing the degradation of its substrates, TRIM15 has also been reported to mediate K63-linked ubiquitination of its substrates, such as TAK1 [ 40 ] and ERK1/2 [ 24 ], and modulate the function of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that TRIM15 promotes APOA1 ubiquitination and degradation in pancreatic cancer [ 11 ]. Liang et al reported that TRIM15 directly targets Keap1 for degradation [ 12 ]. In addition to enhancing the degradation of its substrates, TRIM15 has also been reported to mediate K63-linked ubiquitination of its substrates, such as TAK1 [ 40 ] and ERK1/2 [ 24 ], and modulate the function of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The tripartite motif (TRIM) family member TRIM15 acts as an E3 ligase to mediate the polyubiquitination of substrates in cells [ 11 ]. Dysregulation of TRIM15 contributes to tumor progression in pancreatic cancer and non-small cell lung cancer [ 11 , 12 ]. In this study, we found that TRIM15 was abnormally upregulated in liver cancer cells after treated with TKIs and that this upregulation of TRIM15 contributed to TKI resistance in liver cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tripartite Motif Containing 15 (TRIM15) encodes a member of the Tripartite motif family, which could exhibit E3 ubiquitin ligase activity. TRIM15 could regulate the Wnt/b-catenin signaling pathway and Keap1-Nrf2 pathway and mediate the ubiquitination of APOA1 and ERK to promote the development and progression of cancers such as non-small cell lung cancer, esophageal squamous cell carcinoma, and pancreatic cancer (35)(36)(37). NIMA Related Kinase 6 (NEK6) encodes a kinase, which plays multiple roles in the tumor, including suppression of tumor cell senescence and facilitation of breast cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRIM22 was found to inhibit the Warburg effect in osteosarcoma cells [ 101 ]. In another study, TRIM15 was identified to promote NSCLC progression via Nrf2 stability mediated by promoting Keap1 (Kelch-like ECH associated protein 1) ubiquitination and degradation [ 94 ]. Keap1 is an E3 ubiquitin ligase, which tightly regulates the activity of Nrf2 by targeting it for ubiquitination.…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%
“…The Notch, AMPK, MAPK, and YAP signaling pathways have also been reported to play vital roles in cancer. Knockdown a crucial coactivator of Notch receptors and signal transmission and function, decreases the expression of TRIM13, TRIM32, TRIM44, and TRIM59 especially in T-ALL [ 94 ]. The activation of MAPK enhances TRIM2 protein levels and affectes its binding with Bim, resulting in reduced Bim in tamoxifen-resistant breast cancer cells [ 256 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%